Assembléias de bairro na Argentina: criando espaços de ação política para reconstituir o tecido social - Bogado, Adriana Marcela (Universidade Federal de São Carlos, 2005)
Taking into account the current context of social, political and economic crisis this work consists of a study about the Neighborhood assemblies in Argentina that followed the panelaços2, which happened in the 19th and 20th of December of 2001. The main characteristics of the assemblies are that they promote mechanisms of direct democracy, territorial organization, autonomy in face of political parties and finally for being composed mainly of people belonging to poorer sectors of society. People that never had political engagement, people that protested in the Seventies, people that participate in different political parties, syndicates or social organizations gather weekly in different neighborhoods to debate and generate actions in order to create alternatives to face the crisis and also try to develop spaces where new ways of dealing with politics can take place and thus deepening the process of democratization. Our study aims to describe the Neighborhood assemblies, its beginning and the practices performed, using the participants experience as a starting point. In order to accomplish that the chosen research methodology was Oral History alongside with Participative Observation of the assemblies and also other activities that resulted from these methods. With the objective of broadening the collected data spectrum, we have brought in photographs and a wide range of materials made by the participants as well as the entries in a filed diary. The data gathering was done between January and February of 2004 in two assemblies of the city of Buenos Aires, namely: a Asamblea Popular de San Telmo-Plaza Dorrego e a Asamblea de Palermo Viejo. The Oral History allowed us to rebuild the participants recent memories, those of the beginning of the assemblies, of the initial meetings. On the other hand it also worked as channel for yet another memory that was present inside the participants accounts to come to surface: that of the military dictatorship. Men and women identify the destruction of the social tissue as one of the main consequences of the military dictatorship and the following democratic governs. Beginning with this point of view they started to develop spaces of political action orientated to the reconstruction of this tissue. Hence, we would like to point out some important aspects of the actions of the assemblies, namely: the work with the memories of the repression years, o development of deliberation spaces that eventually enriched the political culture, the political action and solidarity networks with other social movements, the process of (re) signify the publics spaces and its management, the collective work and the accomplishment of activities and projects that aimed to create alternatives in a context of generalized crisis.
Keywords: Movimentos sociais; Assembléias de bairro; Memória; História oral; Argentina; CIENCIAS SOCIAIS APLICADAS